Continuity of care in Ghana: the promise of smart-med - Ogoe, Henry; Agyapong, Odame; Lutterodt, Fredrick Troas (International Journal of Engineering and Technology, 2014)
Individuals tend to receive medical care from different health care providers as they drift from one location to another. Oftentimes, multiple providers operate disparate systems of managing patients’ medical records. These disparate systems, which are unable to share and/or exchange information, have the propensity to create fragmentation of care, which poses a serious threat to the realization of continuity of care in the Ghanaian health care delivery. Continuity of care, which is the ability to seamlessly access, update, and manage patients’ medical information as they visit multiple providers, is a crucial component of quality of care in any health delivery system. The current system of managing patients’ records in Ghana—paper-based—makes continuity of care difficult to actualize. To this end, we have developed a smartcard based personal health records system, SMART-MED, which can effectively promote continuity of care in Ghana. SMART-MED is platform-independent; it can run as standalone or configured to plug into any Java-based electronic medical record system. Results of a lab simulation test suggest that it can effectively promote continuity of care through improved data security, support interoperability for disparate systems, and seamless access and update of patients’ health records. Keywords: Continuity of Care, Fragmentation of Care, Interoperability, Personal Health Records, Smartcard.